Between the “Phanariote Yoke” and the „Jesuitical Yoke”. The 1859–1861 polemics between “Bulgaria” and “The Danubian Swan” journals concerning the issue of the Bulgarian Church - Popek, Krzysztof (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">At the turn of 1850s and 1860s there was a serious discussion inside the Bulgarian Church Movement, which had fallen apart into four parties: national, pro-Turkish moderates, pro-Russian moderates and pro-Uniate. One of the most fervent debates took place between the journals “The Danubian Swan” (edited by Georgi Sava Rakovski, connected with the national party the Church Movement) and “Bulgaria” (published by the leader of pro-Uniate party Dragan Tzankov). The discussions focused on the topics pivotal for the Bulgarian national case: the relation of the Church Movement to the Ottoman Empire, the Patriarchate of Constantinople, the Catholic Church and the Great Powers (especially Russia and France), the problem of the Bulgarian cultural model, the medieval heritage and Christian dogmas. One of those topics concerned the relation of the Church movement to the Ottoman Empire – in general both journals declared loyalty to the Sultan, but the problem mainly concerned the Turkish censorship. “Bulgaria” and “The Dunabian Swan“ agreed that the Patriarchate of Constantinople is the main enemy of Bulgarian interests. Liberating the Bulgarian Church from Greeks was their primary goal. Tzankov wanted to realize this goal in cooperation with the Catholic Church, for Rakovski, instead, the Church Union would lead to the new enslavement of the Bulgarians, who would fall under the “yoke of Jesuits”. That problem was also connected with the search for an ally between the Great Powers: “Bulgaria” wanted to cooperate with France, which was the main patron of Catholicism in the World, whereas “The Dunabian Swan” tried to gain Russian support. The activists of the Church Movement realized that the Union will have a significant impact on the future of the Bulgarian culture. Tzankov was a proponent of the modernization of the Bulgarian society according to Western standards. Rakovski warned that the Union will be the beginning of the collapse of the Bulgarian nation and a betray of its age-old connection with the Orthodox Church. They proved these visions with historical examples – during the discussion the editor of “Bulgaria” created an alternative and false version of the Medieval history of Bulgaria, in which he tried to prove the existence of deep relations between Bulgarians and the Catholic Church. Another important part of the discussion between the journals revolved around Christian dogmas and was based on the old polemics about dogmas lasting since the 9th century between the Western and Eastern Christianity. The arguments used in the articles about the Church Movement by Rakovski and Tzankov only very rarely had a rational character, they were usually based on emotions, stereotypes and the Bulgarian sense of pride.